Spontaneous Regression of Disc Prolapse – An Underlooked Phenomena: A Case Report and Literature Review - Majd Alrayes (Journal of Spine Practice)
Introduction: Intervertebral disc prolapse is a very common abnormality found in the population, that can manifest in a variety of complaints like back pain, radiculopathy, and even to the extent that it might lead to more adverse neurological deficits. Symptoms improve in majority of patients only with conservative treatment. However, some patients may require surgical intervention. In some cases, spontaneous regression of herniated disc can be seen. Thus, the interest in the phenomenon of spontaneous resorption of the herniated discs has increased, which raised the controversy regarding managing such patients. Here, we report a case of a huge lumbosacral spontaneous disc resolution at the level of L5-S1 in which clinical improvement was associated with a significant decrease in the size of a huge, herniated disc. In addition, we performed a comprehensive review of literature of all reported cases of spontaneous disc resolution to provide an updated discussion of such an underlooked phenomena.